The Influence of Interpersonal Behaviors and Population Density on Grip Strength of Elderly People: An Analysis of the Direct vs. Indirect Effects via Social Participation - Lin, Haibo; Ren, Haijun (Frontiers in Public Health, 2021)
The impact of social participation (SP) on the health of the elderly has been widely recognized, and urban-rural differences in social participation have attracted attention. However, few studies discussed the impact of social participation on specific health indicators and the further subdivision of urban-rural differences. The goal of this research is to use the dimensions of the interpersonal behaviours and population density rather than simple urban-rural distinctions to try justifying community differences and compare the direct and indirect effects of these differences on grip strength. This study used data from 15871 respondents aged over 50 years from the China Health and Retirement Longitudinal Study (CHARLS). An SEM (Structural Equation Modelling) analysis was used to explore the joint effect of interpersonal behaviour and population density on social participation and the consequent impact on changes in grip strength and compare the differences among different genders, ages, wealth levels, and family relationships. The results indicated that community differences characterized by interpersonal behaviour and population density have direct effects on grip strength and indirect effects on it through social participation. The conclusion is that the frequency of social activities, such as mah-jong and dancing in the Metropolitan Fringe and county-level cities is higher than that in Metropolitan centres. The high frequency of these activities has a positive and indirect impact on grip strength, and community differences have a more significant impact on women's social participation than men. However, broadly, the direct effect of community differences as defined by interpersonal communication and population density on grip strength is greater than the indirect effect which some other factors through social participation.